(3QTM GdSMGH aj TQM fXe GdMSGHs - (3GdbRhjfj, eMSf Hf eMeO WGgQ, cGf MjG (B1128 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3deG fXe NdGUI GdMSGH GdaGVd (B... (3bhGe GdOjf eMeO GdMSjfj (B.. (3hSeGg fXe GdNdGUI hcGf eY hLGRI fXeg hUZQ MLeg LGeYG (B...s
(3BNQgG (B:s
.. (3bGd GdTGQM (B.. (3gPG BNQ eG GhQOfG LeYg ef GdahGFO GdJj jQMd aj JMbjb ebGUO gPG GdcJGH EdjgG hfeg ef GdaQGFO GdJj jbhd aj age eSGFdg YdjgG (B... (3hcGf GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\21s
(3eYLe GdeDdajf (B3\21s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs